Conception of Raising the Living Standards of Territorial Community Based on the Introduction and Development of New Forms of Innovation and Investment Cooperation Between the Regional Authorities and the Local Community - Popadynets, V.I. (Science and Innovation, 2024)
The main provisions have been formulated for the elaboration, implementation, and development of regional target programs based on new methodological and financial resources for the procurement of the most significant products manufactured by regional corporations in order to ensure a sustainable improvement of the local community living standards.